Problem Analysis in Sub-Assembly Department Using Empathize Design Thinking and Failure Mode Effects Analysis: A Case Study of PT X - Andrian, Fernando Septa; Putrianto, Novenda Kartika (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2023)
PT X is a company that engages in the production of large vehicles, particularly buses. The company currently has a sub-assembly department responsible for providing support materials used in the production process. Within the sub-assembly department, there are several constraints that affect the ongoing production process. These hindrances can lead to various losses for the company. Therefore, a study is being conducted to identify and understand the obstacles present in the sub-assembly department. The problem identification process employs the empathize stage of design thinking, aiming to determine the importance of each problem. To achieve this, a ranking system known as Failure Mode Effects and Analysis is being utilized. The results indicate the existence of six problems within the sub-assembly department. Following the prioritization process, it was determined that the primary issue revolves around inadequate administrative procedures. Based on these findings, an evaluation is planned for the company, specifically focusing on the sub-assembly department. The objective is to promptly address these problems and prevent any significant impacts on the company. This abstract emphasizes the importance of identifying departmental issues and prioritizing immediate solutions.